Adapting to the new sporting goods market era: sportswear company pushing the boundaries of consumer relationship - Matos, Filipe Franco Abreu (2022)
This report is the first part of a two parts report which provides a thorough analysis of Adidas AG’s business and financial performance with the main objective to determine the firm ́s target price and issue a buy/sell/hold recommendation to investors. This paper will follow a comprehensive approach that involves a detailed analysis of key trends in the new normal of the Sporting Goods Industry. It is expected that athleisure, Women's Segment, and especially E-commerce will be the key trends that determine success in this industry. Furthermore, it will be considered the future actions that Adidas AG will take under its new "Own the Game" plan and clarify how the company intends to take advantage of these trends. It is that Adidas' business model will undergo major changes in the years to come, which will bring numerous challenges to the company.